2016
DOI: 10.1159/000444478
|View full text |Cite
|
Sign up to set email alerts
|

Do Public Involvement Activities in Biomedical Research and Innovation Recruit Representatively? A Systematic Qualitative Review

Abstract: Background: Public involvement activities (PIAs) may contribute to the governance of ethically challenging biomedical research and innovation by informing, consulting with and engaging the public in developments and decision-making processes. For PIAs to capture a population's preferences (e.g. on issues in whole genome sequencing, biobanks or genome editing), a central methodological requirement is to involve a sufficiently representative subgroup of the general public. While the existing literature focusses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…They found that the way biobank employees understand and practice engagement activities differed across biobanks and between people working in the same institution 24. Lander et al evaluated how issues of representativeness in public involvement activities were reported in publications 25. Although their study was not restricted to biobanks, 18 (39%) out of 46 analysed publications focused on public involvement in biobank research.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the way biobank employees understand and practice engagement activities differed across biobanks and between people working in the same institution 24. Lander et al evaluated how issues of representativeness in public involvement activities were reported in publications 25. Although their study was not restricted to biobanks, 18 (39%) out of 46 analysed publications focused on public involvement in biobank research.…”
Section: Resultsmentioning
confidence: 99%
“…The latter aspects became evident in particular from the survey respondents' open answers (Q. 19). Also, while (some) guidance on planning and conducting PPI is available from research and PPI institutions, a considerable number of survey respondents mentioned the need for more guidance and a better understanding of "PPI".…”
Section: Resultsmentioning
confidence: 99%
“…Further assessment of PPI activities could be done for instance by contacting research groups leaders either from a specific area of research or more broadly and interviewing them regarding non-published PPI activities. This may also reveal insights about whether reporting/publishing on PPI and particular aspects such as participant recruiting is lacking so far [19] because authors simply do not consider reporting about PPI relevant, or because of actual difficulties with PPI conduct in practice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if reasonable disagreements persist after discussion has been conducted, public deliberation will nevertheless have contributed to legitimacy and fairness because it is based on an aspiration to offer justification for a certain decision. Similarly to developments within deliberative democratic theory, from the first stage which was mostly characterized by normative considerations, the discussion has largely moved towards practice of public deliberation regarding various bioethical issues [3][4][5].…”
Section: Introductionmentioning
confidence: 99%